2005
DOI: 10.1111/j.1365-2133.2005.06687.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the expression of ERBIN and Erb-B2 in normal human skin and cutaneous carcinomas.

Abstract: The subcellular localization of ERBIN in normal human skin is similar to that of Erb-B2 and varies with cell differentiation. Based on our findings and on the biological activities of Erb-B2, it is conceivable that disturbed expression or functioning of ERBIN and Erb-B2 is implicated in the development of the malignant phenotype of BCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 25 publications
0
30
0
2
Order By: Relevance
“…6,13,20,21 HER2 is regulated by many adaptor and scaffolding proteins; for instance erbin, which controls the receptor sorting. 7,11,22 The example being membranous expression in keratinocytes and upper suprabasal layer of normal skin, but cytoplasmic in basal layer. 22 In thyroid cancer, decreasing HER2 expression characterized dedifferentiated parts of poorly differentiated tumors up to immunonegativity in anaplastic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,13,20,21 HER2 is regulated by many adaptor and scaffolding proteins; for instance erbin, which controls the receptor sorting. 7,11,22 The example being membranous expression in keratinocytes and upper suprabasal layer of normal skin, but cytoplasmic in basal layer. 22 In thyroid cancer, decreasing HER2 expression characterized dedifferentiated parts of poorly differentiated tumors up to immunonegativity in anaplastic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…7,11,22 The example being membranous expression in keratinocytes and upper suprabasal layer of normal skin, but cytoplasmic in basal layer. 22 In thyroid cancer, decreasing HER2 expression characterized dedifferentiated parts of poorly differentiated tumors up to immunonegativity in anaplastic carcinoma. 17 In our study, we observed membranous-cytoplasmic HER2 labeling in normal adrenomedullary tissue, developing fetal autonomic neural crest cells and differentiating cells in neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Based on earlier studies that localized Erbin to cell junctions in the suprabasal epidermis, we predicted that DSG1 and Erbin would colocalize in keratinocytes (20). Accordingly, by immunofluorescence, DSG1 and Erbin colocalized in both cultured keratinocytes expressing exogenous DSG1 and human plantar skin, indicating that functional complexes could potentially form under physiological conditions (Figure 2, A-D).…”
Section: Figurementioning
confidence: 99%
“…The screen identified a modulator of ERK signaling known to localize at epidermal cell borders in a differentiation-dependent manner named Erbin (also known as ERBB2IP) (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…We cannot rule out that there is also a minor colocalisation at the plasma membrane, as SARA has been shown to interact with TGFb receptors at the plasma membrane (Di Guglielmo et al, 2003) and ERBIN is also detected at the plasma membrane (Borg et al, 2000). Although the localisation of ERBIN on early endosomes has not been reported previously, individual ERBIN-positive cytosolic vesicles have been described, by immunohistochemistry, in basal cell carcinoma (BCC) (Lebeau et al, 2005), and punctate ERBIN staining has been observed, by immunofluorescence, in proximal dendrites (Calin-Jageman et al, 2007). Taken together, we define ERBIN as a newly identified SARA-interacting protein, which can colocalise with the latter on early endosomes.…”
Section: Discussionmentioning
confidence: 89%